UV-B induced morphogenesis: Four players or a quartet? - Jansen, Marcel A.K. (Landes Bioscience, 2012)
Low levels of ultraviolet (UV)-radiation alter the morphology of plants. UV-B exposure can lead to shorter petioles and shorter, narrower and/or thicker leaf blades. The resulting decrease in leaf area has been associated with inhibitory UV-B effects on biomass accumulation. In Arabidopsis, UV-B effects on leaf area have variously been attributed to altered cell division, cell expansion or combinations of these two processes. A dedicated UV-B sensory system, crosstalk between flavonoids and auxins, endoreduplication and generic Stress Induced Morphogenic Responses (SIMR) have all been proposed to contribute to the UV-B phenotype. Here, we propose that UV-mediated morphogenesis, rather than being controlled by a single regulatory pathway, is controlled by a regulatory blur involving multiple compensatory molecular and physiological feedback interactions.